2021
DOI: 10.1016/j.heliyon.2021.e07874
|View full text |Cite
|
Sign up to set email alerts
|

A review on the indigenous multipurpose agroforestry tree species in Ethiopia: management, their productive and service roles and constraints

Abstract: Tree planting has a long history in Ethiopia and managing indigenous multipurpose trees is widely adopted by farmers, as a dominant feature of agricultural landscapes. Farmers manage different indigenous multipurpose tree species within agroforestry practices. But variability in agroecological conditions causes inconsistency on tree species selection, their intended benefits and ecological services. Management practices and current constraints on them were also the major issues on indigenous multipurpose agrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Among other benefits, farmers used ILFTS for the treatment of various illnesses in humans and livestock, as the study revealed. Lelamo (2021) substantiated the medicinal value of some indigenous multipurpose trees in Ethiopia. Tannins and other secondary metabolites in fodder trees and shrubs contribute to the anthelmintic (Assefa et al., 2018; Hoste et al., 2011; Maroyi, 2017) and antimicrobial property (Assefa et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other benefits, farmers used ILFTS for the treatment of various illnesses in humans and livestock, as the study revealed. Lelamo (2021) substantiated the medicinal value of some indigenous multipurpose trees in Ethiopia. Tannins and other secondary metabolites in fodder trees and shrubs contribute to the anthelmintic (Assefa et al., 2018; Hoste et al., 2011; Maroyi, 2017) and antimicrobial property (Assefa et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Tannins and other secondary metabolites in fodder trees and shrubs contribute to the anthelmintic (Assefa et al., 2018; Hoste et al., 2011; Maroyi, 2017) and antimicrobial property (Assefa et al., 2017). Several authors described the multipurpose of legume fodder trees for their services and products such as biological nitrogen fixation, diversification of livestock's diets, shades, carbon sequestration, bee forage, timber, charcoal, firewood, biodiversity conservation, traditional medicine, pole and post for construction, reduction of greenhouse gas emission, and fence, among others (Dubeux Junior et al., 2017; Franzel et al., 2014; Lelamo, 2021; Meaza & Demssie, 2015). Some of the ILFTS identified in the study resemble those characterised by some authors in Ethiopia (Abera & Yasin, 2018; Derero & Kitaw, 2018; Lelamo, 2021; Shenkute et al., 2012; Sisay et al., 2017; Weldemariam & Gebremichael, 2015) and other east Africa countries (Mtengeti & Mhelela, 2006; Rubanza et al., 2007) probably due to the similarity of the agroclimatic zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivated tree species provide yields for building wood, firewood, animal feed, species, and medicinal plants [212]. The use of native species with multiple benefits needs to be encouraged with research and policy interventions because native trees can maintain biodiversity [213]. The greater the plant diversity in agroforestry, the greater the value of the forest from the yield variety and the environmental benefits.…”
Section: Wo Strategy Wt Strategymentioning
confidence: 99%
“…Over extended periods of time, agroforestry methods have evolved in response to interactions between agroecological conditions, plant diversity, and farmer resources and demand [11,[15][16][17][18]. Te various multipurpose trees and shrubs planted in agroforestry systems can provide the community with a variety of services and goods critical to rural livelihoods [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%